The missing dog is spotted - Kerrin, Jessica Scott (Groundwood Books/House of Anansi Press, 2015)
Trevor Tower doesn't worry too much about being short until he is assigned dog-walking duty with Loyola Louden, the tallest person in his class. But the dogs are a wonderful distraction, and even before Trevor and Loyola vow to solve the mystery of the missing spotted dog, they become good friends.